Bukusu and Amazonian perspectives on harmonious relations with the other - Presbey, Gail M. (2019)
The article follows the theme of dealing with adversaries and conflict resolution. As an exercise in intercultural philosophy, the paper explores the philosophies of two different regions, the Amazon of South America (Jivaro and Yanesha /Amuesha people of Peru) and Western Province of Kenya, East Africa (with focus on the Bukusu people). Exploring the insights of other researchers as well as drawing upon interviews by the author, the article explains each group's philosophy of conflict resolution referencing myths, folktales, proverbs, and interviews with sages. In the case of both communities, practitioners of peace must engage in bravery to reach out to others and address them with a message of peaceful relations. The Yanesha have a founding myth that emphasizes the role of a woman in establishing harmonious relations, whereas the Bukusu folktales emphasize men's leadership.
Keywords: Comparative philosophy; Philosophy; Conflict resolution; Peace; Bukusu (African people) -- Folklore; Amuesha Indians